Histórico dos aparelhos intraorais para tratamento do ronco primário e da Síndrome da Apneia e Hipopneia Obstrutiva do Sono - Reis, Amanda Kimura Lucchesi [UNESP] (2016)
The treatment of the primary snore and obstructive sleep apnea is a dental surgeon's field of work that is not yet being explored intensely, even with the large demand of work that exists. Although the evidence of the matter in the communications' media, it is common to find colleagues with no knowledge of this treatment modality. The diversity of existing devices is also a factor that makes the clinical confused in which adopt and trust. The need of a proximity with the medical class may also be an additional factor to the resistance of interest by the area. The purpose of this study is, trhough a literature review, clarify the advances that these devices have undergone over the years until nowadays so that the clinical can use these benefits safely